Cognition and Its Association with Psychosocial and Occupational Functioning during Treatment with Escitalopram in Patients with Major Depressive Disorder: A CAN-BIND-1 Report: La Cognition Et Son Association Avec Le Fonctionnement Psychosocial Et Professionnel Durant Le Traitement Par Escitalopram Chez Des Patients Souffrant De Trouble Dépressif Majeur: Une Étude Can-Bind-1. (September 2021) - McInerney, Shane J.; Chakrabarty, Trisha; Maciukiewicz, Malgorzata; Frey, Benicio N.; MacQueen, Glenda M.; Milev, Roumen V.; Ravindran, Arun V.; Rotzinger, Susan; Kennedy, Sidney H.; Lam, Raymond W.; ,
Objectives: Major depressive disorder (MDD) is associated with impairments in both cognition and functioning. However, whether cognitive deficits significantly contribute to impaired psychosocial and occupational functioning, independent of other depressive symptoms, is not well established. We examined the relationship between cognitive performance and functioning in depressed patients before and after antidepressant treatment using secondary data from the first Canadian Biomarker Integration Network in Depression-1 study. Methods: Cognition was assessed at baseline in unmedicated, depressed participants with MDD ( n = 207) using the Central Nervous System Vital Signs computerized battery, psychosocial functioning with the Sheehan Disability Scale (SDS), and occupational functioning with the Lam Employment Absence and Productivity Scale (LEAPS). Cognition ( n = 181), SDS ( n = 175), and LEAPS ( n = 118) were reassessed after participants received 8 weeks of open-label escitalopram monotherapy. A series of linear regressions were conducted to determine (1) whether cognitive functioning was associated with psychosocial and occupational functioning prior to treatment, after adjusting for overall depressive symptom severity and (2) whether changes in cognitive functioning after an 8-week treatment phase were associated with changes in psychosocial and occupational functioning, after adjusting for changes in overall symptom severity. Results: Baseline global cognitive functioning, after adjusting for depression symptom severity and demographic variables, was associated with the SDS work/study subscale (β = −0.17; P = 0.03) and LEAPS productivity subscale (β = −0.17; P = 0.05), but not SDS total (β = 0.19; P = 0.12) or LEAPS total (β = 0.41; P = 0.17) scores. Although LEAPS and SDS scores showed significant improvements after 8 weeks of treatment ( P < 0.001), there were no significant associations between changes in cognitive domain scores and functional improvements. Conclusion: Cognition was associated with occupational functioning at baseline, but changes in cognition were not associated with psychosocial or occupational functional improvements following escitalopram treatment. We recommend the use of more comprehensive functional assessments to determine the impact of cognitive change on functional outcomes in future research.